The Concept of Islamic Education Syed Muhammad Naquib al-Attas and Ahmad Syafi'i Ma'arif, Its Relevance to the Implementation of Inclusive Learning in the Independent Curriculum - M. Rizki Saputra; Mutohharun Jinan; Muhammad Wildan Shohib (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This research aims to: to find out the Concept of Islamic Education according to Syed Muhammad Naquib al-Attas and its relevance to providing inclusive learning in the mardeka curriculum to find out the Concept of Islamic Education according to Ahmad Syafi'i Ma'arif, and its relevance to providing inclusive learning in the mardeka curriculum To find out the Islamic Education Concept of Syed Muhammad Naquib al-Attas and Ahmad Syafi'i Ma'arif as well as its relevance to providing inclusive learning in the mardeka curriculum. This type of research is descriptive qualitative research, that is, the data collected is in the form of words, images, not numbers. The research approach used is a qualitative research approach. The primary sources in this research are works written by the figures studied themselves, in this research are Syed Muhammad Naquib Al-Attas and Ahmad Syafi'i Ma'arif. The research results show that the concept of Islamic education according to Al-Attas leads to the value of content in Islamic education. Where in the concept Al-Attas uses the concept of ta'adib. The concept prioritizes good manners or good human behavior. Ahmad Syafi'i Ma'arif's thinking about the concept of education is relevant to the free learning curriculum. This is based on the first, the educational goals initiated by Ahmad Syafi'i Ma'arif view that in essence it seeks to create students who have character and competence that is useful for society.